Peningkatan Literasi Digital Guru Dalam Pembelajaran Blended Learning - Fitriani Fitriani; Putri Ade Rahma Yulis; Nurhuda Nurhuda; Sukarni Sukarni; Affriyani Gunita; Siti Cholijah (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This service activity aims to increase teacher digital literacy in blended learning. The method used in service activities was the assistance carried out by observation, preparation, implementation, and evaluation. The dedication partner was Rumbio Jaya State Senior High School 4. The instrument for evaluating this activity used a questionnaire which was analyzed descriptively. The results of the community service that had been carried out and evaluated showed an increase in teacher digital literacy. This increase was shown by the teacher's understanding before the activity, from an average score of 3.11 to an average of 3.30 after the activity was carried out. However, even though there has been an increase, teachers still need to maximize their ability to use technology to support the implementation of blended learning better.